TRANSPORT OF SUSPENDED SOLIDS FROM A KARSTIC TO AN ALLUVIAL AQUIFER: THE ROLE OF THE KARST/ALLUVIUM INTERFACE - Massei N.; Lacroix M.; Wang H.Q.; Mahler B.J.; Dupont J.P. (My University, 2002)
This study focuses on the coupled transport of dissolved constituents and particulates, from their infiltration on a karst plateau to their discharge from a karst spring and their arrival at a well in an alluvial plain. Particulate markers were identified and the transport of solids was characterised in situ in porous and karstic media, based on particle size analyses, SEM, and traces. Transport from the sinkhole to the spring appeared to be dominated by flow through karst: particulate transport was apparently conservative between the two sites, and there was little difference in the overall character of the particle size distribution of the particulates infiltrating the sinkhole and of those discharging from the spring. Qualitatively, the mineralogy of the infiltrating and discharging material was similar, although at the spring an autochthonous contribution from the aquifer was noted (chalk particles eroded from the parent rock by weathering). In contrast, transport between the spring and the well appears to be affected by the overlying alluvium: particles in the water from the well, showed evidence of considerable size-sorting. Additionally, SEM images of the well samples showed the presence of particles originating from the overlying alluvial system; these particles were not found in samples from the sinkhole or the spring. The differences between the particulates discharging from the spring and the well indicate that the water pumped from the alluvial plain is coming from the karst aquifer via the very transmissive, complex geologic interface between the underlying chalk formation and the gravel at the base of the overlying alluvial system.
Keywords: GEOLOGIC INTERFACE; ALLUVIUM; KARST; TURBIDITY; PARTICLE TRANSPORT; SIZE DISTRIBUTION; CONTAMINANT VECTOR